The Improved Interpolating Complex Variable Element-Free Galerkin Method for Two-Dimensional Elastic Problems - Deng, Yajie; Dai, Ying (Acta mechanica solida Sinica, 2022)
An improved interpolating complex variable element-frees Galerkin (IICVEFG) method for the two-dimensional elastic problems is developed. This method is based on the improved interpolating complex variable moving least-squares (IICVMLS) method and the integral form of the elastic problems. In the IICVEFG method, the proposed shape function has the interpolating feature. Therefore, the essential boundary conditions can be exerted directly. Additionally, the unnecessary terms in the discrete matrices are removed, which results in a set of concise formulas. This method is verified by analyzing three elastic examples under different constraints and loads. The numerical results show that the IICVEFG method is superior in precision and efficiency to other non-interpolating meshless methods.